2015
DOI: 10.1038/srep08111
|View full text |Cite
|
Sign up to set email alerts
|

An injectable acoustic transmitter for juvenile salmon

Abstract: Salmon recovery and the potential detrimental effects of dams on fish have been attracting national attention due to the environmental and economic implications. In recent years acoustic telemetry has been the primary method for studying salmon passage. However, the size of the existing transmitters limits the minimum size of fish that can be studied, introducing a bias to the study results. We developed the first acoustic fish transmitter that can be implanted by injection instead of surgery. The new injectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 24 publications
1
56
0
Order By: Relevance
“…It is therefore important to include untagged control fish in studies, whenever possible (laboratory/tanks/ponds), or, for instance, by comparing with less invasive tagging methods like dyemarking, coded wire tagging, or PIT-tagging in field studies. In general, it seems that external tagging of juvenile salmonids can be done, but the experiences are not as good as they are for the surgical implant or tag injection [39] techniques. Also perciforms (including Percidae, Teraponidae, Centrarchidae) can be vulnerable to external tagging, but here the results vary among species and studies.…”
Section: Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore important to include untagged control fish in studies, whenever possible (laboratory/tanks/ponds), or, for instance, by comparing with less invasive tagging methods like dyemarking, coded wire tagging, or PIT-tagging in field studies. In general, it seems that external tagging of juvenile salmonids can be done, but the experiences are not as good as they are for the surgical implant or tag injection [39] techniques. Also perciforms (including Percidae, Teraponidae, Centrarchidae) can be vulnerable to external tagging, but here the results vary among species and studies.…”
Section: Survivalmentioning
confidence: 99%
“…Thus, since the life of small electronic tags is usually low (but see [39]), external tagging can be preferred due to lower acute health effects compared to surgical implantation, where a longer recovery period may be evident. In a field study on Chinook salmon smolts, Brown et al [40] observed 10 % tag loss 9-17 days after tagging, as well as a high proportion of tags that were loose or displaced.…”
Section: Cebidichthys Violaceusmentioning
confidence: 99%
“…10 This design reduces both the tag burden and deployment costs. The transmitter has a diameter of 3.38 mm, length of 15.00 mm, dry weight of 217 mg, and an average source level in the front 180…”
Section: Acoustic Telemetrymentioning
confidence: 99%
“…Because the circuit board situated behind the PZT tube ( Figure 1) blocks the sound waves emitted from the back of the tube, the acoustic signals propagating in this direction are considered largely "wasted" as they will have a much lower probability of being detected. 10 To use the input electrical energy more efficiently, the center of the inner circle of the tube is purposely offset from that of the outer circle along the tube's radial direction by 0.15 mm, so that the tube has a gradually changing wall thickness. The thicker portion of the tube faces the circuit board and the thinner portion of the tube is oriented towards the front of the transmitter.…”
Section: A Piezoelectric Transducermentioning
confidence: 99%
“…Transmitters with frequency and pulse codes that permit fish to be individually identified can provide detailed information on both the large-and smallscale behavior of fish (Berman and Quinn, 1991). A recent example is the Juvenile Salmon Acoustic Telemetry System that is being used to monitor the survival and behavior of juvenile salmonids migrating downstream through eight large hydroelectric facilities within the Federal Columbia River Power System to the Pacific Ocean (McMichael et al, 2010;Weiland et al, 2011;Deng et al, 2011;and Deng et al, 2015).…”
Section: Fisheriesmentioning
confidence: 99%